Evaluation of recycled concrete aggregate backfill for geosynthetic-reinforced MSE walls. Issue 4 (7th August 2019) - Soleimanbeigi, A.; Tanyu, B. F.; Aydilek, A. H.; Florio, P.; Abbaspour, A.; Dayioglu, A. Y.; Likos, W. J.
Abstract : Mechanical and hydraulic properties of recycled concrete aggregate (RCA) were evaluated for use as backfill in mechanically stabilized earth (MSE) walls. Large-scale drained triaxial tests, direct shear tests and pullout tests were performed to obtain mechanical properties of RCA interacting with various geosynthetics. Long-term filtration (LTF) tests were performed to evaluate hydraulic conductivity of RCA-geotextile systems. Results showed that the RCA had an internal friction angle of 49°, which was within the typical range. The RCA-uniaxial geogrid had the highest interface friction angle of 36° – and the interface friction angles of RCA-biaxial geogrid, RCA-nonwoven geotextile, and RCA-woven geotextile were 32°, 26° and 22°, respectively. Reinforced RCA showed comparable pullout capacity to reinforced sand. No slippage was observed between the RCA and geotextiles or geogrids, and the failures occurred mainly due to rupture of the geotextiles and geogrids during the pullout test. Results of the LTF tests showed that, over a filtration period of 2500 h, the ratio of mean hydraulic conductivity of RCA only to that of RCA-nonwoven geotextile and RCA-woven geotextile systems remained between 0.91 and 3.2, suggesting that the clogging of the geotextiles with RCA was minimal.